Traffic Light Innovation for Strengthening the Profile of Pancasila Students at SDN 10 Kota Barat - Yes Anggreni; Aliya Ningsi Lasimpala; Sapna Nursakia S Kalui; Femmy FS Lumentut; Abdul Rahmat (Periodica Journal, 2022)
The learning model is basically a form of learning that is illustrated from start to finish which is typically presented by the teacher as a unified whole. Learning models must be seen from two aspects, namely process and product. The process aspect refers to learning that is able to create fun learning situations (joyful learning) and encourages students to actively learn and think creatively. The product aspect refers to whether learning is able to achieve its goals, namely improving students' abilities according to the specified standards of ability and competence, in this case reflected in student learning outcomes. In this activity we conducted a situation analysis or observation at SDN 10 Kota Barat. Analysis of the physical condition of the SDN 10 Kota Barat school is divided into 2 floors, namely floors 1 and 2. The first floor has several study rooms, namely classrooms 1, 2, 3, 4 along with the operator's room, teacher's room and school principal's room. secondly there are class 5 and class 6 and there are several other rooms. traffic lights are made to raise awareness in driving on the highway so that unwanted things such as accidents do not occur
Keywords: Innovation; Enhancing; Profile Of Pancasila Student; rooms